Autotransplantation of wisdom tooth in the alveolus of extracted first mandibular molar - Čolić Snježana; Brajović Ružica (Serbian Medical Society - Dental Section, Belgrade, 2022)
Dental autotransplantation is a surgical procedure where tooth or dental germ is transffered from one position to another, within the same person. This way an edentulous area after extraction can be successfully restored without the need of other more invasive approaches. This procedure is recommended in young individuals who have lost permanent molars due to caries complications and have an impacted third molar as a potential donor tooth. The aim of this report is to present a successful transplantation of wisdom tooth into the alveolus of the first mandibular molar in a case of a young individual.